The Fathom for Good and Evil: Decoding Religious Meaning System in Antonio Campos’ The Devil All the Time (2020) - ‘Izzah, Lina Mawaddatul; Pratama, Rifka (Culturalistics: Journal of Cultural, Literary, and Linguistic Studies, 2024)
Religion and humans are like salt and pepper, they are inseparable. The former becomes an integral part to define the lives of the latter. In some cases, religion is perceived as a tool to construct system of meaning. Utilizing Silberman’s paradigm, this article tries to uncover the manifestation of religion as a groundwork of meaning system in human life within The Devil All the Time (2020) by Antonio Campos. A qualitative method is adopted, with data sourced from library research encompassing both written materials such as books and academic journals and visual media specifically the movie itself. The findings reveal that religion incarnates as meaning system through various elements – self and world belief, contingencies, expectations, goals, actions, and emotions. The concept of religious meaning system is exemplified by several characters who are directly tangent to the religious practices.